2018
DOI: 10.1038/s41467-018-06377-w
|View full text |Cite
|
Sign up to set email alerts
|

The chromatin remodeler RSF1 controls centromeric histone modifications to coordinate chromosome segregation

Abstract: Chromatin remodelers regulate the nucleosome barrier during transcription, DNA replication, and DNA repair. The chromatin remodeler RSF1 is enriched at mitotic centromeres, but the functional consequences of this enrichment are not completely understood. Shugoshin (Sgo1) protects centromeric cohesion during mitosis and requires BuB1-dependent histone H2A phosphorylation (H2A-pT120) for localization. Loss of Sgo1 at centromeres causes chromosome missegregation. Here, we show that RSF1 regulates Sgo1 localizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 47 publications
4
20
0
Order By: Relevance
“…Some of these MeDEGs are involved in tumorigenesis. For instance, SGOL1, a member of the shugoshin family of proteins, is thought to protect centromeric cohesion during mitosis, and its dysregulation at centromeres can lead to chromosome missegregation and miotic arrest [40, 41]. Mu et al found that SGOL1 expression levels are higher in prostate cancer tissues, and SGLO1 knockdown results in the inhibition of tumor cell proliferation, migration, and invasion [42].…”
Section: Discussionmentioning
confidence: 99%
“…Some of these MeDEGs are involved in tumorigenesis. For instance, SGOL1, a member of the shugoshin family of proteins, is thought to protect centromeric cohesion during mitosis, and its dysregulation at centromeres can lead to chromosome missegregation and miotic arrest [40, 41]. Mu et al found that SGOL1 expression levels are higher in prostate cancer tissues, and SGLO1 knockdown results in the inhibition of tumor cell proliferation, migration, and invasion [42].…”
Section: Discussionmentioning
confidence: 99%
“…Centromeric HDAC1, H2A-pT120 and Sog1 localization was restored in RSF1-KO cells expressing the C-terminal region (aa 627–1441) or C-terminal region (aa 982–1441). All the results imply that the C-terminal region (aa 627–1441) or C-terminal region (aa 982–1441) of RSF1 can interact with and recruit HDAC1 to centromeres to maintain centromere cohesion [ 45 ] (Fig. 3 h).…”
Section: Rsf1 Interacts With and Recruits Hdac1 To Centromeres To Protect Centromeric Cohesionmentioning
confidence: 99%
“…In this regard, the mitotic role of Remodeling and spacing factor1 (RSF1), a member of the ISWI family of ATPases, is informative. Like ARID2, RSF1 is required for the centromeric deposition of PLK1 45 and promotes centromeric H2AT120P 46 . The latter activity is achieved by suppressing H2A acetylation.…”
Section: Main Textmentioning
confidence: 99%